CURSOS ON-LINE DO PROGRAMA ESCREVENDO O FUTURO: VOZES QUE SE DEPOSITAM E QUE SE CALAM EM UMA POLÍTICA PÚBLICA DE FORMAÇÃO DE PROFESSORES PARA O ENSINO DA LÍNGUA PORTUGUESA NO BRASIL - Nadai, Gisele Santos de (2020)
The thesis integrates the studies of the line of research in Education and Language of the graduate program in Education of the Federal University of Espirito Santo, regarding the researches that go over public policies about the teaching of the Portugues